Law and visual arts: image, imaginary, and imagination in Law - Simioni, Rafael Lazzarotto (2024)
This paper aims to discuss the relationship between image, imaginary, and imagination in law, based on eight possible contributions that the language of visual arts can offer to the legal field. The central issue is to observe how legal formalism values only positivist forms of knowledge and establishes predominantly instrumental relationships within legal culture. Using an analytical methodology and the technique of literature review, primarily grounded in the notion of function/performance from Niklas Luhmann’s social systems theory. The expected outcome is to highlight significant contributions from studies in law and visual arts to the development of a movement that values imagination, creativity, intelligence, and culture in the legal field.